A Comprehensive Review of Oral Surgical Techniques for the Extraction of Retained and Fractured Dental Roots: Clinical Indications, Procedural Approaches, and Postoperative Outcomes - Al Shakes, Ali Mahdi Abdullah; Mohammed Hussain Alabbad; Waseem Hassan Mansour Aridhi; Jawharah Farraj Aldawsari; Mosheera Suliman Almutairi; Mada Mohammad Alotaibj; Khalid Tharwi Alshammari; Ahmed Essa Ahmed Dallak; Reem Mohammad Alhumaidan; Fatimah Saad Alotaibi; et al. (Saudi Journal of Medicine and Public Health, 2025)
Background: Retained and fractured dental roots transform routine exodontia into complex surgical scenarios with elevated risks due to anatomical variability, proximity to vital structures, and limited coronal purchase. A rigorous understanding of root morphology, case selection, and tissuepreserving techniques is essential to optimize outcomes. Aim: To synthesize clinical indications, contraindications, operative armamentarium, techniques, and complication profiles for the extraction of retained/fractured dental roots, highlighting principles that enhance predictability and patientcentered results. Methods: Narrative review of anatomical considerations, decision frameworks (indications vs. contraindications), equipment and personnel requirements, preoperative preparation including imaging (2D radiographs, CBCT), operative strategies (closed/open retrieval; periotomes, piezosurgery; endodontic file/needle engagement; vertical extraction systems), and complication mitigation. Results: Retained roots warrant removal for infection, pain, periodontal breakdown, restorative/implant planning, and associated pathology; however, removal may be deferred when risks to IAN or sinus, extensive bone loss, root submergence objectives, or patient preference outweigh benefits. Team readiness, profound anesthesia, enhanced visualization, and judicious escalation from closed to open techniques reduce morbidity. CBCT improves risk assessment near the sinus and mandibular canal. Minimally invasive tools (periotomes, piezosurgery, vertical systems) can preserve alveolar architecture but require careful case selection. Conclusion: Safe, efficient retrieval hinges on anatomyguided planning, imaginginformed risk stratification, tissueconserving instrumentation, disciplined force control, and coordinated team performance. Referring to a different method when proximity to critical anatomy or technical complexity elevates risk.